Self-Management: Reducing Social Media - Afnur, Amilza; Wicaksono, Awang Setiawan (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The development of technology from time to time will continue to grow rapidly with changes, especially in the field of communication and information. The development of communication and information has caused many communication delivery media to emerge that have been designed to be able to convey information in a very easy way, one of which is social media. Social media provides many conveniences that make its users feel safe in cyberspace for a long time. Most social media users are teenagers, who are easily carried away by global developments, the desire to get information, and have difficulty distinguishing between good and bad to be used as a reference for behavior. This study aims to direct students in reducing the use of social media during classroom learning. The research method used is the one group pretest-posttest experimental approach, pretest and posttest are carried out by racing against indicators of social media addiction behavior. Based on the results, the self-management strategy can reduce the use of social media in class XI students at SMK Nurul Islam Manyar.Perkembangan teknologi dari zaman ke zaman akan terus semakin pesat dengan adanya perubahan terutama pada bidang komunikasi dan informasi. Perkembangan komunikasi dan informasi ini menyebabkan banyak sekali bermunculan media penyampaian komunikasi yang sudah didesain untuk dapat menyampaikan informasi dengan cara yang sangat mudah, yaitu salah satunya media sosial. Media sosial memberikan banyak kemudahan yang membuat penggunanya bisa merasa aman di dunia maya dalam jangka waktu yang lama. Sebagian besar pengguna media sosial  adalah  remaja, yang mudah terhanyut dalam perkembangan global,  keinginan untuk mendapatkan informasi, dan kesulitan membedakan mana yang baik dan mana yang buruk untuk dijadikan acuan perilaku. Penelitian ini bertujuan untuk mengarahkan siswa dalam mengurangi penggunaan media sosial saat pembelajaran di kelas. Metode penelitian yang digunakan yaitu pendekatan eksperimen one group pretest-posttest, pretest dan posttest dilakukan dengan berpacu pada indikator perilaku kecanduan media sosial. Berdasarkan hasil yang dilakukan strategi self management dapat mengurangi penggunaan media sosial pada siswa kelas XI di SMK Nurul Islam Manyar.